PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH DALAM PEMBELAJARAN MENULIS TEKS LAPORAN - Weni Risa Meigita; Andiopenta Purba; Hilman Yusra; Warni Warni; Oky Akbar (Universitas Negeri Makassar, 2024)
This research aims to determine the influence of the problem-based learning model in writing report texts based on observations of class VIII students at Ahmad Dahlan Middle School, Jambi City. The research uses quantitative methods with a quasi-experimental type of research. Data collection techniques include tests, observation, and documentation. The subjects of this research were class VIII students at Ahmad Dahlan Middle School, Jambi City. The population in this study was in class VIII of Ahmad Dahlan Middle School, Jambi City, and there were four classes totaling 122 students. The sample in this study was class VIII A, consisting of 30 students, and class VIII B, consisting of 29 students. The research results show that the use of the problem-based learning model influences student learning outcomes in writing observation report texts. The ability to write student observation report text increases due to the use of a learning-based model. This was proven in the posttest, where the control class got an average score of 77.55. Meanwhile, the experimental class posttest was 84.96. In the control class posttest, the lowest score was 67, while the lowest score in the experimental class posttest was 80, and the highest score in the control class posttest was 89, which experienced an increase in the experimental class posttest, namely 92.